Relationship Between MSMES and Financial Institutions in West Aceh - Yasrizal, Yasrizal; Harmaini, Harmaini; Manan, Afni Abd; Mahrizal, Mahrizal (Jurnal Ilmiah Teunuleh, 2023)
This study aims to analyze the relationship between Micro, Small, and Medium Enterprises (MSMEs) and financial institutions concerning loan repayment. The data used in this research is both qualitative and quantitative primary data. The study collected a sample of 100 micro and small enterprises distributed in Aceh Barat. The data analysis employed probability and binary logit models.The results of the data analysis indicate that loan repayment difficulties, interest rates, collateral, and own capital have a negative impact on MSMEs' access to financial institutions. The variable that has the most significant impact on MSMEs' accessibility to financial institutions is the interest rate, followed by collateral and own capital. To improve MSMEs' access to financial institutions, government attention is crucial. Providing low-interest credit for MSMEs, easing collateral requirements, and promoting the establishment of various Islamic financial institutions are essential steps. This is because the growth of MSMEs contributes to increased employment opportunities and economic growth.